Revisiting pathophysiology of benign paroxysmal positional vertigo: a review - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of peripheral vertigo. There are several possible underlying causes of BPPV, although the idiopathic form is the most common. BPPV is characterized by brief recurrent episodes of vertigo that are triggered by changes in head position. Although BPPV is a benign vestibular disorder, it can be a severe and disabling problem for some of patients. The pathophysiology of BPPV is still unclear. The pathophysiology for BPPV is complex and the underlying mechanism is related to free-floating debris/otoliths in the semicircular canal (canalolithiasis) or debris/otoliths attached to the cupula (cupulolithiasis). These otolith/debris are originally accumulated after detachment from the neuroepithelium of the utricular macula secondary to degeneration. BPPV can occur following other vestibular disorders. In the majority of cases, the triggering factors are unknown. Some patients of BPPV have a history of previous inner ear diseases such as Meniere’s disease or acute unilateral peripheral vestibulopathy. This clinical entity is well-defined in medical literature and usually effectively treated by certain physical maneuvers. However, the pathophysiology is still obscure and is being critically discussed in this article, which reviews the details pathological mechanism for BPPV. This review article will discuss that aging, trauma, migraine, Meniere’s disease, vestibular neuronitis, and vitamin-D deficiency are the most commonly investigated etiopathological factors resulting in BPPV.